Composite nucleating agent for regulating and controlling preparation of nano calcium carbonate
Through the coordinated regulation method of composite nucleating agent and modifier, the problems of incomplete modification and abnormal morphology of nano calcium carbonate prepared by traditional in situ carbonization method are solved, and the efficient dispersion and stability of nano calcium carbonate is achieved, which improves compatibility with organic matrix and reduces energy consumption and production costs.
Patent Information
- Application Number
- CN202510892831.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-30
- Publication Date
- 2025-08-15
AI Technical Summary
When preparing nano calcium carbonate in situ, there are problems such as incomplete modification, abnormal morphology and unstable crystal structure, especially the coexistence of elliptical and spindle shapes, and the gas-liquid mass transfer efficiency is low, the particle agglomeration is serious, and the particle size distribution is uneven.
A coordinated regulation method of the composite nucleation agent (zinc chloride and sucrose) and the introduction of dispersed modifiers after nucleation is adopted. By precisely controlling the timing and order of introduction of the modifier, combining high-speed stirring and mixed gases, heterophasic nucleation is promoted, the initial grains are refined, and the stable lattice structure is formed.
Significantly improve the dispersion and morphological uniformity of nano calcium carbonate, improve compatibility with organic matrix, reduce agglomeration, reduce energy consumption and production costs, and achieve efficient dispersion modification and morphological regulation of nano calcium carbonate.
Smart Images

Figure CN120483220A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano-calcium carbonate preparation, in particular to a composite nucleating agent for regulating the preparation of nano-calcium carbonate. Background Art
[0002] As an important functional inorganic material, nano-calcium carbonate has been widely used in rubber, plastics, papermaking, daily chemicals, medicine and environmental protection due to its excellent physical and chemical properties, including high specific surface area, good biocompatibility and environmental friendliness. It is worth noting that more than 90% of application scenarios require good interfacial compatibility between nano-calcium carbonate and organic matrices. However, the surface of unmodified nano-calcium carbonate is rich in hydrophilic hydroxyl groups, which has significant surface property differences from non-polar or weakly polar organic materials. This incompatibility often leads to interfacial defects in composite materials.
[0003] In the existing technology, surface modification is the main method to improve the compatibility of inorganic fillers / organic matrices. Current research focuses on post-modification processes, including dry modification and wet modification, but there are common problems such as high energy consumption and uneven modification. In contrast, in-situ modification technology is increasingly attracting attention from academia and industry due to its advantages in modification uniformity, production efficiency and cost control. However, in the gas-liquid-solid heterogeneous system for the preparation of nano-calcium carbonate by carbonization, the traditional in-situ modification method faces the following technical bottlenecks: (1) low gas-liquid mass transfer efficiency; (2) serious particle agglomeration; (3) difficulty in morphology control; and (4) uneven particle size distribution.
[0004] For example, the patent with publication number CN 110128851A, entitled "A Method for Preparing Hydrophobic Nano-Calcium Carbonate," achieved in-situ modification in a microreactor. However, due to the premature addition of the surface modifier to the calcium hydroxide solution, that is, its introduction before nucleation, the modification reaction was incomplete, resulting in abnormal product morphology, with irregular morphologies such as elliptical and spindle shapes appearing simultaneously, and insufficient crystal structure stability.
[0005] In response to the above technical deficiencies, the present invention achieves efficient dispersion modification and morphology control of nano-calcium carbonate by adopting a preparation method that adopts a composite nucleating agent and introduces a dispersing modifier after nucleation to synergistically control the dispersibility of nano-calcium carbonate. Summary of the Invention
[0006] In view of the shortcomings of the existing technology, the main purpose of the present invention is to provide a preparation method of nano-calcium carbonate based on the coordinated regulation of a composite nucleating agent, which solves the problems of incomplete modification, abnormal morphology (coexistence of elliptical / spindle shapes) and unstable crystal structure in the traditional in-situ carbonization method for preparing nano-calcium carbonate.
[0007] Another object of the present invention is to provide a composite nucleating agent, whereby the nucleating agent can promote heterogeneous nucleation, refine the initial grains, and form a stable lattice structure of nano-calcium carbonate crystals.
[0008] Another object of the present invention is to provide an innovative order of adding surface modifiers so that the added modifiers act only on the particle surface and do not interfere with the intrinsic growth direction of the crystals, thereby ensuring uniform product morphology.
[0009] The present invention also provides a composite nucleating agent, which can promote heterogeneous nucleation, refine the initial grains, and form a stable lattice structure of nano-calcium carbonate crystals. The technical solution is as follows:
[0010] The nucleating agent is a composite nucleating agent of zinc chloride and sucrose, the ratio of zinc chloride to sucrose is 5:1-1:1, and the content of the nucleating agent is 0.1wt%-5wt% of the total amount of the calcium hydroxide slurry.
[0011] The nucleating agent is uniformly mixed with calcium hydroxide slurry and stirred at high speed to obtain slurry 1; the concentration of the calcium hydroxide slurry is 5 wt%-10 wt%.
[0012] The high-speed stirring has a rotation speed of 800 rpm-1200 rpm.
[0013] The present invention provides a preparation method of nano-calcium carbonate based on the coordinated regulation of a composite nucleating agent, which solves the problems of incomplete modification, abnormal morphology (coexistence of elliptical and spindle shapes) and unstable crystal structure in the traditional in-situ carbonization method for preparing nano-calcium carbonate.
[0014] The technical solution is as follows:
[0015] A preparation method of nano calcium carbonate based on the coordinated regulation of a composite nucleating agent comprises the following steps:
[0016] (1) Preparing slurry 1: uniformly mixing calcium hydroxide slurry and nucleating agent, and stirring at high speed to obtain slurry 1; the concentration of the calcium hydroxide slurry is 5 wt%-10 wt%;
[0017] (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 to perform carbonization reaction. When the slurry begins to gel and become viscous, add a surface modifier into the reaction system to obtain slurry 2;
[0018] (3) Crystal guidance: When the pH of slurry 2 is 10±0.5, add the crystal guidance agent and stir until the pH reaches 6.5±0.5, then stop aeration;
[0019] (4) Preparation of modified nano-calcium carbonate: After the crystal-guided solution is heated at 50-80°C and stirred for 0.5-2 h, the precipitate is collected by filtration or centrifugation, washed, and dried to obtain modified nano-calcium carbonate.
[0020] Preferably, the nucleating agent is a composite nucleating agent of zinc chloride or zinc sulfate and sucrose, and the content of the nucleating agent is 0.1 wt%-5 wt% of the total amount of the calcium hydroxide slurry.
[0021] Preferably, the ratio of zinc chloride or zinc sulfate to sucrose is 5:1-1:1;
[0022] Preferably, in steps (1) to (3), the mixed gas is continuously introduced during the reaction process and high-speed stirring is continuously performed.
[0023] Preferably, the carbonization reaction temperature is 0°C-50°C.
[0024] Preferably, the mixed gas is a mixture of carbon dioxide and an inert gas, and the flow rate ratio of carbon dioxide to inert gas in the mixed gas is 1:3.
[0025] Preferably, the surface modifier is a composite modifier of copolymer salt, saponified sodium stearate and coconut oil, and the mass ratio of the copolymer salt to saponified sodium stearate and coconut oil is 5-1:1-5:0.1-0.5;
[0026] The copolymer salt is one of a polystyrene-carboxylic anhydride functional group copolymer, a polystyrene-N-phenylmaleimide-carboxylic anhydride functional group terpolymer, a polyacrylonitrile-styrene-butadiene rubber-carboxylic anhydride functional group terpolymer, and a polybutadiene-acrylonitrile-styrene-carboxylic anhydride functional group tetrapolymer, and the salt is obtained by ring-opening under alkaline conditions;
[0027] The alkali solution is sodium hydroxide solution.
[0028] Preferably, the saponified sodium stearate is a product obtained by saponifying stearic acid in a sodium hydroxide solution at a molar ratio of 1:1.
[0029] Preferably, the amount of the surface modifier is 0.1 wt%-2 wt% of the total amount of the calcium hydroxide solution.
[0030] Preferably, the crystal directing agent is sulfuric acid, and the molar ratio of sulfuric acid to calcium ions is 0.01:1-0.001:1.
[0031] Preferably, the high-speed stirring has a rotation speed of 800 rpm-1200 rpm.
[0032] Preferably, the drying temperature is 60° C. and the drying time is 24 h to 48 h.
[0033] The present invention also provides an innovative order for adding surface modifiers, so that the added modifiers act only on the particle surface and do not interfere with the intrinsic growth direction of the crystals, thereby ensuring uniform product morphology. The technical solution is as follows:
[0034] The surface modifier is added after the nucleation stage;
[0035] In the nucleation stage, the calcium hydroxide slurry and the nucleating agent are uniformly mixed and stirred at high speed to obtain slurry 1, and then the mixed gas is continuously introduced into the carbonization reaction. When the conductivity value of the slurry is the lowest and the reaction system is in a gelled state, a large number of highly active nano-calcium carbonate crystals are generated in the reaction system, and nucleation is completed at this time.
[0036] Since the present invention adopts the above technical solution, it has the following beneficial effects:
[0037] By precisely controlling the timing of modifier introduction, optimizing the synergistic effect of nucleating agents and crystal-directing agents, and combining a composite modifier system, the present invention significantly improves the dispersibility, morphological uniformity, and compatibility of nano-calcium carbonate with organic matrices. Compared to existing technologies, the present invention has the following advantages:
[0038] 1. Significantly improve the dispersibility of nano calcium carbonate and reduce agglomeration
[0039] When preparing nano-calcium carbonate by traditional in-situ carbonization, the introduction of surface modifiers before nucleation can easily lead to incomplete modification, abnormal morphology (coexistence of elliptical and spindle shapes), and unstable crystal structure. The present invention effectively inhibits agglomeration by the following means:
[0040] (1) Accurately control the timing of introducing the modifier: add the modifier when the slurry begins to gel and become viscous (i.e., the system gels and a large amount of nano-calcium carbonate crystals are generated). At this time, the surface activity of the particles is the highest, and the modifier can be evenly coated to reduce subsequent agglomeration.
[0041] (2) Composite nucleating agents (zinc chloride or zinc sulfate) optimize the nucleation process: Zn²⁺ can promote heterogeneous nucleation and refine the initial grains, while sucrose inhibits excessive particle growth, making the final product particle size distribution narrower.
[0042] (3) High-speed stirring to enhance mass transfer: Combined with the mixed flow rate ratio of CO2 and inert gas (1:3), the gas-liquid mass transfer efficiency is improved and agglomeration caused by excessive local concentration is avoided.
[0043] 2. Improve the compatibility of nano-calcium carbonate with organic matrix
[0044] The surface of unmodified nano-calcium carbonate is rich in hydrophilic hydroxyl groups (-OH), which makes it poorly compatible with non-polar organic materials (such as rubber and plastics). The present invention achieves efficient surface hydrophobization through the use of a composite modifier (copolymer salt + saponified sodium stearate + coconut oil):
[0045] (1) Copolymer salts (such as polystyrene-carboxylic anhydride functional group copolymers): After the polystyrene-carboxylic anhydride functional group copolymer is ring-opened under alkaline conditions, the carboxylate (—COO⁻) strongly binds to Ca²⁺ to form a strong chemical bonding layer, thereby improving the modification stability.
[0046] (2) Saponified sodium stearate: long chain alkyl (C 17 H 35 —) Provide hydrophobicity, synergistically coat the particles with the copolymer, and significantly reduce the interfacial energy with the organic matrix.
[0047] (3) Coconut oil: Adding a small amount of coconut oil can further improve the dispersibility of the modifier in the system and ensure the uniformity of the modification.
[0048] (4) Modification uniformity: Post-nucleation modification avoids the problem of incomplete coating caused by premature addition of modifiers in traditional in-situ modification.
[0049] 3. Achieve precise control of crystal shape and avoid abnormal morphology: After nucleation, the nano-calcium carbonate microcrystals have initially formed a stable lattice structure. At this time, the addition of modifiers only acts on the particle surface and will not interfere with the intrinsic growth direction of the crystal, thereby ensuring uniform product morphology.
[0050] 4. Carbonization and modification are carried out simultaneously, eliminating the need for subsequent modification steps and reducing energy consumption and production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Attachment Figure 1 The present invention is a flow chart for preparing hydrophobic nano calcium carbonate.
[0052] Attachment Figure 2 This is the TEM image of Example 1 of the present invention.
[0053] Attachment Figure 3 This is the TEM image of Comparative Example 1 of the present invention.
[0054] Attachment Figure 4 This is the TEM image of Comparative Example 2 of the present invention.
[0055] Attachment Figure 5 This is the TEM image of Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0056] The following describes the technical solutions in the embodiments of the present invention in detail with reference to several embodiments and accompanying drawings. It is apparent that the embodiments described are only some of the embodiments of the present invention, not all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are considered to fall within the scope of protection of the present invention.
[0057] Example 1
[0058] (1) Preparation of slurry 1: Calcium hydroxide slurry with a concentration of 5 wt% was uniformly mixed with a nucleating agent prepared by zinc chloride and sucrose in a ratio of 5:1, and the mixed gas was continuously introduced and stirred at 800 rpm to obtain slurry 1; the content of the nucleating agent was 0.1 wt% of the total amount of the calcium hydroxide slurry;
[0059] (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 and perform carbonization reaction at 0°C. When the slurry begins to gel and become viscous, add a surface modifier to the reaction system to obtain slurry 2; the amount of the surface modifier is 0.1 wt% of the total amount of the calcium hydroxide solution;
[0060] The surface modifier is a composite modifier made of copolymer salt, saponified sodium stearate and coconut oil in a mass ratio of 5:1:0.1;
[0061] The copolymer salt is a salt obtained by ring-opening a polystyrene-carboxylic anhydride functional group copolymer under sodium hydroxide conditions; the saponified sodium stearate is a product obtained by saponifying stearic acid in a sodium hydroxide solution at a molar ratio of 1:1;
[0062] (3) Crystal guidance: Continue to introduce mixed gas and stir at 800 rpm. When the pH of slurry 2 reaches 10, add sulfuric acid and stir until the pH reaches 6, then stop aeration; the molar ratio of sulfuric acid to calcium ion is 0.01:1.
[0063] The mixed gas used in this embodiment is a mixture of carbon dioxide and helium, and the flow rate ratio of carbon dioxide to helium in the mixed gas is 1:3.
[0064] (4) Preparation of modified nano-calcium carbonate: The crystal-guided solution was heated and stirred at 50°C for 0.5 h, and the precipitate was collected by filtration or centrifugation, washed, and dried at 60°C for 24 h to obtain modified nano-calcium carbonate.
[0065] Example 2
[0066] (1) Preparation of slurry 1: Calcium hydroxide slurry with a concentration of 10 wt% was uniformly mixed with a nucleating agent prepared by zinc sulfate and sucrose in a ratio of 1:1, and the mixed gas was continuously introduced and stirred at a high speed of 1200 rpm to obtain slurry 1; the content of the nucleating agent was 5 wt% of the total amount of the calcium hydroxide slurry;
[0067] (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 and perform carbonization reaction at 50°C. When the slurry begins to gel and become viscous, add a surface modifier to the reaction system to obtain slurry 2; the amount of the surface modifier is 2 wt% of the total amount of the calcium hydroxide solution;
[0068] The surface modifier is a composite modifier of copolymer salt, saponified sodium stearate and coconut oil, and the mass ratio of the copolymer salt to saponified sodium stearate and coconut oil is 1:5:0.5;
[0069] The copolymer salt is a polystyrene-N-phenylmaleimide-carboxylic anhydride functional group terpolymer, which is ring-opened under sodium hydroxide solution to obtain a salt; the saponified sodium stearate is a product obtained by saponifying stearic acid in a sodium hydroxide solution at a molar ratio of 1:1.
[0070] (3) Crystal guidance: Continue to introduce mixed gas and stir at a high speed of 1200 rpm. When the pH of slurry 2 reaches 10.5, add sulfuric acid and stir until the pH reaches 7, then stop aeration; the molar ratio of sulfuric acid to calcium ion is 0.001:1.
[0071] The mixed gas used in this embodiment is a mixture of carbon dioxide and argon, and the flow rate ratio of carbon dioxide to argon in the mixed gas is 1:3.
[0072] (4) Preparation of modified nano-calcium carbonate: The crystal-guided solution was heated and stirred at 80°C for 2 h, and the precipitate was collected by filtration or centrifugation, washed, and dried at 60°C for 48 h to obtain modified nano-calcium carbonate.
[0073] Example 3
[0074] (1) Preparation of slurry 1: Calcium hydroxide slurry with a concentration of 8 wt% was uniformly mixed with a nucleating agent prepared by zinc chloride and sucrose in a ratio of 3:1, and the mixed gas was continuously introduced and stirred at a high speed of 1000 rpm to obtain slurry 1; the content of the nucleating agent was 3 wt% of the total amount of the calcium hydroxide slurry;
[0075] (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 and perform carbonization reaction at 25°C. When the slurry begins to gel and become viscous, add a surface modifier to the reaction system to obtain slurry 2; the amount of the surface modifier is 1 wt% of the total amount of the calcium hydroxide solution;
[0076] The surface modifier is a composite modifier of copolymer salt, saponified sodium stearate and coconut oil, and the mass ratio of the copolymer salt to saponified sodium stearate and coconut oil is 3:2:0.3;
[0077] The copolymer salt is a salt obtained by ring-opening a tetrapolymer of polybutadiene-acrylonitrile-styrene-carboxylic anhydride functional groups in a sodium hydroxide solution; the saponified sodium stearate is a product obtained by saponifying stearic acid in a sodium hydroxide solution at a molar ratio of 1:1.
[0078] (3) Crystal guidance: Continue to introduce mixed gas and continue stirring at high speed. When the pH of slurry 2 is 10, add sulfuric acid and stir until the pH reaches 6.5, then stop aeration; the molar ratio of sulfuric acid to calcium ion is 0.005:1.
[0079] The mixed gas used in this embodiment is a mixture of carbon dioxide and neon, and the flow rate ratio of carbon dioxide to neon in the mixed gas is 1:3.
[0080] (4) Preparation of modified nano-calcium carbonate: The crystal-guided solution was heated and stirred at 70°C for 1 h, and the precipitate was collected by filtration or centrifugation, washed, and dried at 60°C for 30 h to obtain modified nano-calcium carbonate.
[0081] Example 4
[0082] (1) Preparation of slurry 1: Calcium hydroxide slurry with a concentration of 5 wt% was uniformly mixed with a nucleating agent prepared by zinc sulfate and sucrose in a ratio of 4:1, and the mixed gas was continuously introduced and stirred at a high speed of 800 rpm to obtain slurry 1, wherein the content of the nucleating agent was 0.1 wt% of the total amount of the calcium hydroxide slurry;
[0083] (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 and perform carbonization reaction at 30°C. When the slurry begins to gel and become viscous, add a surface modifier to the reaction system to obtain slurry 2; the amount of the surface modifier is 2 wt% of the total amount of the calcium hydroxide solution;
[0084] The surface modifier is a composite modifier of copolymer salt, saponified sodium stearate and coconut oil, and the mass ratio of the copolymer salt to saponified sodium stearate and coconut oil is 5:1:0.5;
[0085] The copolymer salt is a terpolymer of polyacrylonitrile-styrene-butadiene rubber-carboxylic anhydride functional groups, which is ring-opened under sodium hydroxide conditions to obtain a salt; the saponified sodium stearate is a product obtained by saponifying stearic acid in a sodium hydroxide solution at a molar ratio of 1:1.
[0086] (3) Crystal guidance: Continue to introduce mixed gas and stir at a high speed of 1000 rpm. When the pH of slurry 2 reaches 9.5, add sulfuric acid and stir until the pH reaches 7, then stop aeration; the molar ratio of sulfuric acid to calcium ion is 0.008:1.
[0087] The mixed gas used in this embodiment is a mixture of carbon dioxide and argon, and the flow rate ratio of carbon dioxide to argon in the mixed gas is 1:3.
[0088] (4) Preparation of modified nano-calcium carbonate: The crystal-guided solution was heated and stirred at 50°C for 0.5 h, and the precipitate was collected by filtration or centrifugation, washed, and dried at 60°C for 35 h to obtain modified nano-calcium carbonate.
[0089] Example 5
[0090] (1) Preparing slurry 1: uniformly mixing a 10 wt% calcium hydroxide slurry with a nucleating agent prepared by zinc chloride and sucrose in a ratio of 5:1, continuously introducing the mixed gas, and continuously stirring at a high speed of 1000 rpm to obtain slurry 1, wherein the content of the nucleating agent is 0.1 wt% to 5 wt% of the total amount of the calcium hydroxide slurry;
[0091] (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 and perform carbonization reaction at 50°C. When the slurry begins to gel and become viscous, add a surface modifier to the reaction system to obtain slurry 2; the amount of the surface modifier is 0.1 wt% of the total amount of the calcium hydroxide solution;
[0092] The surface modifier is a composite modifier of copolymer salt, saponified sodium stearate and coconut oil, and the mass ratio of the copolymer salt to saponified sodium stearate and coconut oil is 1:5:0.1;
[0093] The copolymer salt is a polystyrene-carboxylic anhydride functional group copolymer, which is ring-opened under sodium hydroxide conditions to obtain a salt; the saponified sodium stearate is a product obtained by saponifying stearic acid in a sodium hydroxide solution at a molar ratio of 1:1.
[0094] (3) Crystal guidance: Continue to introduce mixed gas and continue stirring at a high speed of 1000 rpm. When the pH of slurry 2 reaches 10, add sulfuric acid and stir until the pH reaches 6, then stop aeration; the molar ratio of sulfuric acid to calcium ion is 0.01:1-0.001:1.
[0095] The mixed gas used in this embodiment is a mixture of carbon dioxide and neon, and the flow rate ratio of carbon dioxide to neon in the mixed gas is 1:3.
[0096] (4) Preparation of modified nano-calcium carbonate: The crystal-guided solution was heated and stirred at 80°C for 0.5 h, and the precipitate was collected by filtration or centrifugation, washed, and dried at 60°C for 48 h to obtain modified nano-calcium carbonate.
[0097] Comparative Example 1: The preparation method is the same as that of Example 1, except that a dispersant is added to slurry 1.
[0098] Comparative Example 2: The preparation method is the same as that of Example 1, except that the nucleating agent is changed to single sucrose.
[0099] Comparative Example 3: The preparation method is the same as that of Example 1, except that the nucleating agent is changed to a single zinc salt.
[0100] Morphology Dispersed state Average particle size / nm <![CDATA[Specific surface area / m 2 / g]]> Activation Example 1 oval Good dispersibility 30.1 37.8 96.5% Example 2 oval Good dispersibility 34.4 33.4 99.1% Example 3 oval Good dispersibility 33.2 35.3 98.9% Example 4 oval Good dispersibility 27.9 39.3 98.4% Example 5 oval Good dispersibility 38.1 30.9 99.8% Comparative Example 1 Oval and spindle-shaped reunion 791.7 10.4 93.5% Comparative Example 2 oval Slight reunion 40.2 30.1 76.1% Comparative Example 3 oval Slight reunion 31.7 36.8 85.3%
[0101] The results of the implementation cases and comparative cases show that the process of adding a dispersant after nucleation, the composite nucleating agent, and the type of dispersant used in this patent have significant advantages. The above strategy effectively regulates the crystallization behavior of nano-calcium carbonate. The modified nano-calcium carbonate particles prepared by this patent have uniform morphology and a narrow particle size distribution. At the same time, they have high activation and good dispersibility. The modified nano-calcium carbonate prepared by this process has excellent comprehensive performance and provides a reliable technical path for the industrial production of highly stable and easily dispersible nanomaterials.
Claims
1. A composite nucleating agent for regulating the preparation of nano calcium carbonate, characterized in that: The composite nucleating agent consists of a zinc-containing compound and sucrose.
2. The composite nucleating agent according to claim 1, wherein The composition ratio of the zinc-containing compound to sucrose is 5:1-1:
1.
3. The composite nucleating agent according to claim 1 or 2, wherein The zinc-containing compound is zinc chloride or zinc sulfate.
4. A preparation method of nano calcium carbonate based on the coordinated regulation of a composite nucleating agent, characterized in that: The surfactant is added after nucleation.
5. The preparation method according to claim 4, wherein The specific steps include: (1) Preparing slurry 1: uniformly mixing calcium hydroxide slurry and composite nucleating agent, and stirring at high speed to obtain slurry 1; the concentration of the calcium hydroxide slurry is 5 wt%-10 wt%; (2) Preparation of slurry 2: Continuously introduce mixed gas into slurry 1 to perform carbonization reaction. When the slurry begins to gel and become viscous, add a surface modifier into the reaction system to obtain slurry 2; (3) Crystal guidance: When the pH of slurry 2 is 10±0.5, add the crystal guidance agent and stir until the pH reaches 6.5±0.5, then stop aeration; (4) Preparation of modified nano-calcium carbonate: After the crystal-guided solution is heated at 50-80 °C and stirred for 0.5-2 h, the precipitate is filtered or centrifuged, washed, and dried to obtain modified nano-calcium carbonate.
6. The preparation method according to claim 5, wherein The content of the composite nucleating agent is 0.1 wt%-5 wt% of the total amount of the calcium hydroxide solution.
7. The preparation method according to claim 5, wherein In the steps (1) to (3), the mixed gas is continuously introduced during the reaction and high-speed stirring is continuously performed.
8. The preparation method according to claim 5 or 7, characterized in that The mixed gas is a mixture of carbon dioxide and inert gas, and the flow rate ratio of carbon dioxide to inert gas in the mixed gas is 1:
3.
9. The preparation method according to claim 5, wherein The surface modifier is a composite modifier of copolymer salt, saponified sodium stearate, and coconut oil, and the mass ratio of the copolymer salt, saponified sodium stearate, and coconut oil is 5-1:1-5:0.1-0.5; The copolymer salt is one of a polystyrene-carboxylic anhydride functional group copolymer, a polystyrene-N-phenylmaleimide-carboxylic anhydride functional group terpolymer, a polyacrylonitrile-styrene-butadiene rubber-carboxylic anhydride functional group terpolymer, and a polybutadiene-acrylonitrile-styrene-carboxylic anhydride functional group tetrapolymer, and the salt is obtained by ring-opening under alkaline conditions; The alkali solution is sodium hydroxide solution.
10. The preparation method according to claim 5 or 9, characterized in that: The amount of the surface modifier is 0.1wt%-2wt% of the total amount of the calcium hydroxide solution.
Citation Information
Patent Citations
Preparation method of hydrophobic nano calcium carbonate
CN110128851A